2004
DOI: 10.1300/j013v40n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a Culturally Sensitive Cervical Health Survey: A Community-Based Participatory Approach

Abstract: Cervical cancer mortality rates are higher for Great Plains Native American women than for Caucasian women and other Native women. Messengers for Health, a project based on the Apsáalooke (Crow Indian) reservation, utilizes a lay health advisor approach to decrease cervical cancer screening barriers, increase knowledge regarding screening and prevention, and increase the proportion of women receiving Pap tests among Apsáalooke women aged 18 and older. This project utilizes a community-based participatory resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…Also, indigenous communities have historically been reluctant to participate in research projects because traditional research methods, which emphasize the researcher as "the expert," have not engaged indigenous communities in designing and implementing research projects (25). CBPR has been identifi ed as an effective and essential strategy for conducting research with indigenous peoples because of its emphasis on community participation to build ownership of research projects and community-based interventions as well as empowering the community to address its health disparities (26,27).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Also, indigenous communities have historically been reluctant to participate in research projects because traditional research methods, which emphasize the researcher as "the expert," have not engaged indigenous communities in designing and implementing research projects (25). CBPR has been identifi ed as an effective and essential strategy for conducting research with indigenous peoples because of its emphasis on community participation to build ownership of research projects and community-based interventions as well as empowering the community to address its health disparities (26,27).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Although efforts to increase screening rates among this population of women have had some success (Brant, Fallsdown, & Iverson, 1999;Kottke & Trapp, 1998;Lanier, Kelly, & Berner, 1999;Smith, Christopher, & McCormick, 2004), there is minimal understanding of what influences AI women's breast and cervical cancer screening decisions or how these influencing factors may differ from those of the majority White population. The study being reported here begins to address these questions.…”
mentioning
confidence: 99%
“…In particular, literature on the processes involved in creating or adapting measures for research with Alaska Natives and American Indians is extremely limited. As Smith, Christopher, & McCormick (2004) note, “Although some of the extant literature on survey research with Native Americans has mentioned the importance of addressing the issues of cultural sensitivity and appropriateness in survey development and implementation, the research is sparse in terms of providing detailed description of these surveys and methods used for survey development” (p. 71).…”
Section: Culture In Measurement Development and The Culture Of Measurmentioning
confidence: 99%
“…They typically review item content, providing input on both substance and wording (e.g. Smith et al, 2004; Stevens, Cornell et al, 1999). They can also be engaged more broadly in the selection of measurement variables and elaborations of the broader dimensions of culturally congruent theoretical constructs.…”
Section: Intergroup Processes Involving Researchers and Community Memmentioning
confidence: 99%